SHARIA COMPLIENCE AKAD BERBASIS NATURAL UNCERTAINTY CONTRACT (NUC) LEMBAGA KEUANGAN MIKRO SYARIAH DI KABUPATEN JEPARA - Susilo, Edi; Anam, A. Khoirul (al-Uqud : Journal of Islamic Economics, 2018)
Financing in Sharia Micro Financing Institutions (BMT) is dominated by certainty contracts, as it has less risk than syirkah contract like Mudharabah or Musyarakah based on Natural Uncertainty Contract (NUC). Implementation constraints syirkah contracts exist on both parties, financial institutions and clients. due to lack of financial reports, honesty and transparency of the client's business (asismetric information). The Client gives a business report if the results obtained are small or equivalent to the bank interest rate, but if the business profit is good, then the profit share must be high. This research is a qualitative descriptive analytical research, to see the implementation of syirkah contract on Sharia Micro Finance Institution (BMT) in Jepara Regency and its syariah compliance based on DSN-MUI fatwa. The results showed that BMT in Jepara regency can not fulfill the compliance of shariah contract of Natural Uncertanty Contract (NUC) due to high risk, human resource capability and low comprehension and lack of client's financial report.